Spatial Position Influences Perception of Slope from Graphs. (July 2014) - Parrott, Stacey; Guzman-Martinez, Emmanuel; Ortega, Laura; Grabowecky, Marcia; Huntington, Mark D; Suzuki, Satoru
We routinely examine linear trends from bar graphs and scatterplots while taking a science class, attending a business presentation, or reading a magazine article. Graphs are placed in different positions on a page or a presentation slide for aesthetic considerations. However, because left and right positions tend to be associated with lower and higher values in the conventional depiction of numerical values, we hypothesized that the perception of positive and negative slopes may be influenced by the placement of a graph. Using a visual search task, with each display containing four bar graphs or scatterplots (one per quadrant), we have demonstrated that the detection of a negative slope is selectively slowed in the upper-right quadrant (for both bar graphs and scatterplots), whereas the detection of a positive slope is selectively slowed in the upper-left quadrant (for bar graphs only). These results suggest that an upper-right position is incompatible with perceiving negative slopes and an upper-left position is incompatible with perceiving positive slopes. Although the origin of these specific associations is unclear, our results have implications for where to place a graph depending on the slope it displays.